Assessment of clinical depression in abdominally obese subjects with periodontal disease - Sheetal Acharya; Anurag Satpathy; Rajdeep Beura; Pratiti Datta; Utkalika Das; Pranab Mahapatra (Wolters Kluwer Medknow Publications, 2022)
Background: Depression is a commonly prevailing condition that goes undetected in clinical settings. Both abdominal obesity and periodontal disease have a bearing on mental health and have an impact on the quality of life. Objective: To assess the level of clinical depression in abdominally obese subjects with periodontal disease. Methods: Two hundred and ten subjects with a mean age of 37.45 ± 9.59 years (males = 117; females = 93) were grouped as per their abdominal obesity and periodontal status and assessed for their clinical depression levels (mental health) using the Centre for Epidemiologic Studies-Depression Scale (CES-D). Collected data were analysed. Results: The clinical depression score significantly varied in subjects with different periodontal status in both non-obese (F (2,102) = 113.66, P < 0.0001) and abdominally obese subjects (F (2,102) = 132.04, P < 0.001). Significantly higher depression score was demonstrated in healthy (P < 0.001), gingivitis (P < 0.001), and periodontitis (P < 0.001) groups in abdominally obese subjects. Conclusion: Clinical depression is significantly associated with abdominal obesity and periodontal disease in subjects with abdominal obesity and severe periodontal disease demonstrating higher depression scores.